Grey matter alterations in subclinical depression, anxiety and insecure attachment: A voxel-based morphometry study - Kiiski, Jere (My University, 2021)
The aim of this study was to investigate grey matter alterations in subclinical depression, anxiety and insecure attachment. Attachment is an inborn drive to create and maintain emotional relationships, through which individuals feel safe and protected. It can be categorically divided into secure and insecure attachment styles. Insecure adult romantic attachment has been linked with a range of behavioral problems such as depression, anxiety, aggression and attention deficit hyperactivity disorder. Studying subclinical depressive and anxiety symptoms could help in understanding the pathophysiology of these disorders and it could also improve early diagnostics and treatment. The subject data used in this study comprised of healthy control groups from previous studies done in Turku PET Centre, University of Turku. Subjects underwent T1-weighted magnetic resonance imaging (MRI) and completed questionnaires measuring depression (BDI-II), anxiety (STAI) and insecure social attachment (ECR-R). ECR-R divides insecure attachment further into avoidant and anxious attachment styles. The correlation between brain GM density and questionnaire scores was measured using voxel-based morphometry, which is a method for automatic quantification of grey (and white) matter densities from T1-weighted magnetic resonance images. A new common neurological substrate was found for subclinical depression and insecure attachment. Both subclinical depression and avoidant attachment were negatively associated with GM density in the midline of the brain (especially in the anterior cingulate and superior medial prefrontal cortex). This finding suggests that the midline of the brain has a role in the pathophysiology of depression and avoidant attachment as well. Subclinical anxiety was positively associated with GM density in areas of the brain that have previously been linked with fear and anxiety: in the temporal lobe (including fusiform gyrus, amygdala, hippocampus and cerebellum). These findings can be used to improve early diagnostics of depression and anxiety and to improve current neuromodulatory interventions in these disorders.

Tutkimuksen tarkoituksena oli tutkia aivojen harmaan aineen muutoksia subkliinisessä masennuksessa, ahdistuksessa ja turvattomassa kiintymyksessä. Kiintymyksellä tarkoitetaan yksilön tarvetta luoda ja ylläpitää emotionaalisia suhteita muihin ihmisiin ja se voidaan jakaa turvattomaan ja turvalliseen kiintymystyyliin. Turvattoman kiintymyksen on todettu korreloivan positiivisesti masennuksen ja ahdistuksen kanssa. Subkliinisen masennuksen, ahdistuksen ja turvattoman kiintymyksen tutkiminen voi auttaa masennuksen ja ahdistuksen patofysiologian selvittämisessä ja se voi myös parantaa näiden sairauksien varhaisdiagnostiikkaa ja hoitoa. Tutkimuksessa käytettiin koehenkilöinä Turun PET-keskuksen aikaisempien tutkimusten terveitä kontrollihenkilöitä, joilla ei todettu aikaisempia psykiatrisia sairauksia. Koehenkilöiden aivot kuvattiin T1-magneettikuvauksella ja he vastasivat BDI-II-masennusseulakyselyyn, STAI-ahdistusseulakyselyyn ja ECR-R-kiintymyssuhdekyselyyn. ECR-R jakaa turvattoman kiintymyksen kahteen eri luokkaan: välttelevään ja ahdistuneeseen kiintymykseen. Aivojen harmaan aineen ja kyselylomakkeiden pisteiden välistä korrelaatiota mitattiin vokselipohjaisen morfometrian avulla, joka automaattisesti mittaa harmaan ja valkean aineen T-1-magneettikuvista. Tutkimuksessa subkliininen masennus ja välttelevä kiintymys olivat molemmat negatiivisesti yhteydessä harmaan aineen tiheyteen aivojen keskilinjan alueella, anteriorisessa pihtipoimussa ja superomediaalisella prefrontaalisella korteksilla. Tämä viittaa siihen, että aivojen keskilinjan rakenteilla on merkitys sekä masennuksen, että välttelevän kiintymyksen patofysiologiassa. Subkliininen ahdistus oli positiivisesti yhteydessä harmaan aineen tiheyteen rakenteissa, jotka ovat aiempien tutkimusten perusteella liitetty pelkoon ja ahdistukseen; muun muassa käpylisäkkeessä, hippokampuksessa ja pikkuavioissa. Ahdistunut kiintymys ei ollut statistisesti merkitsevästi yhteydessä harmaan aineen määrään aivoissa. Näiden löydösten avulla voidaan parantaa tulevaisuudessa masennuksen ja ahdistuksen varhaisdiagnostiikkaa sekä kehittää nykyisiä neuromodulatorisia hoitomuotoja.
Keywords: depression, anxiety, attachment, grey matter